Impact of Cluster Front Line Demonstrations on Yield and Economics of Toria in Tirap District of Arunachal Pradesh, India - , Abhimanyu Chaturvedi; , Geric Bagra; , N. K. Mishra; , V. K. Pandey (Archives of Current Research International, 2024)
The Cluster Front Line Demonstration (CFLD) program, launched by Ministry of Agriculture and Farmer's Welfare, Government of India, New Delhi nder the National Mission on Oilseed and Oil Palm (NMOOP). The KVK Tirap carried out CFLD on Toria on 80 ha between 2017 and 2018, benefiting 200 individuals spread over 18 villages in the district that was specifically chosen. Primary data served as the study's primary source. The purpose of the study is to examine how the Cluster Front Line Demonstration by Krishi Vigyan Kendra, Tirap, has affected the district's socioeconomic situation, adoption and technology gap, and adoption patterns of both beneficiaries and non-beneficiaries. According to the study, cluster front-line demonstrations of tested technologies can significantly improve the yield potential and net income from oilseed farming while also raising the income levels of the participating farmers. In comparison to farmers' practices, the CFLDs reported higher average gross returns (Rs. 38560 and Rs 44812) and net returns (Rs. 18686 and Rs 19991) with a cost: benefit ratio (2.12 and 2.34); indicating the technology's economic viability.